Kelulut Honey Modulates Skeletal Health and Bone-Related Molecular Markers in Rats Fed a High-Carbohydrate and High-Fat Diet - Sophia Ogechi Ekeuku; Kumeshini Sukalingam; Mohd Fahami Nur Azlina; Fairus Ahmad; Kok-Yong Chin; Elvy Suhana Mohd Ramli (Life, 2026)
Background: High-carbohydrate high-fat (HCHF) diets have been associated with oxidative stress, impaired bone remodelling, and deterioration of skeletal integrity. Kelulut honey (KH), a stingless bee honey rich in antioxidant compounds, has demonstrated protective effects against bone loss; however, its effects on bone density, biomechanical properties, antioxidant status, and bone-related molecular markers remain incompletely understood. (2) Methods: Male Wistar rats were assigned to sham, negative control (NC), or KH-treated groups (200, 400, and 600 mg/kg). The NC and KH groups received an HCHF diet for 24 weeks, with KH administered during the final 12 weeks. Bone microarchitecture was evaluated using micro-computed tomography, bone mineral density (BMD) by dual-energy X-ray absorptiometry, and biomechanical properties by three-point bending. Antioxidant enzyme activities, serum bone turnover markers, and bone-related gene expression were also assessed. (3) Results: HCHF feeding reduced BMD, load, stress, Young’s modulus, gluthatione peroxidase (GPx) activity, and superoxide dismutase (SOD) activity while increasing strain, displacement, serum C-terminal telopeptide of type 1 collagen (CTX-1) and receptor activator of nuclear factor-κB (RANK) levels, and runt-related transcription factor 2 (Runx2) expression. KH supplementation improved bone health by dose-dependently enhancing antioxidant defences, significantly increasing GPx and SOD activities, while catalase (CAT) activity was elevated at 600 mg/kg. The 400 mg/kg dose improved trabecular microarchitecture by increasing trabecular number, connectivity density and cortical area/total tissue area. KH also improved biomechanical properties, increasing load, stress, stiffness, and Young’s modulus while reducing displacement. Furthermore, KH attenuated HCHF-induced increases in Runx2 mRNA and RUNX2 protein and reduced osterix (Sp7), integrin Subunit Alpha 5 (Itga5), and calcitonin receptor (Calcr) mRNA expression. However, serum CTX-1 remained elevated in all KH-treated groups. (4) Conclusions: Overall, the findings suggest that KH may have potential as a natural intervention for mitigating diet-associated skeletal alterations, although further studies are required to clarify the underlying mechanisms.